2014
DOI: 10.1155/2014/145973
|View full text |Cite
|
Sign up to set email alerts
|

Sintering and Hardness Behavior of Fe-Al2O3 Metal Matrix Nanocomposites Prepared by Powder Metallurgy

Abstract: The present paper reports the investigations on sintering and hardness behavior of Fe-Al 2 O 3 Metal Matrix Nanocomposites (MMNCs) prepared by Powder Metallurgy (P/M) route with varying concentration of Al 2 O 3 (5-30 wt%). The MMNC specimens for the present investigations were synthesized by ball milling, followed by compaction and sintering in an inert atmosphere in the temperature range of 900-1100 ∘ C for 1-3 hours using Powder Metallurgy route. Phase and microstructures of the specimens were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Peaks of the XRD plot were matched with JCPDS data files of iron and aluminum oxide compounds. It was found from the JCPDS files that the present composition contains iron (Fe), aluminum oxide (Al 2 O 3 ) and iron aluminate (FeAl 2 O 4 ) phases, respectively [21,24]. The iron aluminate phase formation takes place due to reactive sintering.…”
Section: Density Hardness and Deformation Measurementmentioning
confidence: 91%
See 2 more Smart Citations
“…Peaks of the XRD plot were matched with JCPDS data files of iron and aluminum oxide compounds. It was found from the JCPDS files that the present composition contains iron (Fe), aluminum oxide (Al 2 O 3 ) and iron aluminate (FeAl 2 O 4 ) phases, respectively [21,24]. The iron aluminate phase formation takes place due to reactive sintering.…”
Section: Density Hardness and Deformation Measurementmentioning
confidence: 91%
“…Mixed powder was compacted at a constant load of seven tons followed by sintering in an argon atmosphere at a temperature of 1100 • C for 1 h. After sintering, the compacts were machined on gap or extension type lathe machine so as to achieve the h/d ratio of less than 1 (h = 9 mm, d = 15.2 mm; h/d = 0.59), equal to 1 (h = 12.8 mm, d = 12.8 mm; h/d = 1.0) and greater than 1 (h = 16 mm, d = 11.3 mm; h/d = 1.42). The detailed nomenclature of the specimens sintered at different temperatures and times is discussed in our recent publication [21]. A nomenclature e.g., 5AFe1100(1) is given to a particular specimen in the present case.…”
Section: Preparation Of Test Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 11, the EDX results of 5A2SF1200 (3) indicate the formation of Fe-Si within the sample with 66.89% iron and silicon as 33.11% silicon content. Spectrum 5 shows the variation within the materials homogeniously throughout as 70.98% iron, 5.48% silicon, and 8.11% of aluminium throughout the sample.…”
Section: Scanning Electron Microscopymentioning
confidence: 96%
“…Formation of nano-iron aluminate and nano-iron zirconium oxide phase improves the hardness, wear, deformation, and corrosion properties of the composites significantly. Formation of these nanophases and their characteristics depend on sintering temperature and time [14][15][16][17][18][19]. Literature studies revealed that there are few reports on using zirconium dioxide (ZrO 2 ) as the reinforcement material in iron matrix [20].…”
Section: Introductionmentioning
confidence: 99%